2012
DOI: 10.1124/jpet.112.194456
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Receptor Kinetics on the Onset and Duration of Action and the Therapeutic Index of NVA237 and Tiotropium

Abstract: Studies under nonphysiological conditions suggest that long receptor residency time is responsible for the 24-h duration of action of the long-acting muscarinic antagonist (LAMA) tiotropium. Our aim was to determine how clinically relevant dissociation rates under more physiological conditions influence the differences in onset of action between tiotropium and 3-[(cyclopentylhydroxyphenylacetyl oxy]-1,1-dimethyl-pyrrolidinium bromide (NVA237), a once-daily dry-powder formulation of the LAMA glycopyrronium brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 42 publications
7
93
0
4
Order By: Relevance
“…Within this group of compounds, the half-lives of ipratropium were the shortest. Recently, Sykes et al (2012) suggested that "physiological" assay conditions, in particular the sodium ion concentration of the incubation medium, can markedly reduce M3 mAChR residence times by as much as 10-fold, e.g., the half-life of tiotropium decreased from 462 minutes in the absence of sodium to 46 minutes in the presence of sodium. Nonetheless, the trends for M3 versus M2 mAChR dissociation seem to be a characteristic that is common to this group of pharmacophores.…”
Section: Discussionmentioning
confidence: 99%
“…Within this group of compounds, the half-lives of ipratropium were the shortest. Recently, Sykes et al (2012) suggested that "physiological" assay conditions, in particular the sodium ion concentration of the incubation medium, can markedly reduce M3 mAChR residence times by as much as 10-fold, e.g., the half-life of tiotropium decreased from 462 minutes in the absence of sodium to 46 minutes in the presence of sodium. Nonetheless, the trends for M3 versus M2 mAChR dissociation seem to be a characteristic that is common to this group of pharmacophores.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies designed to assess the kinetics of unlabeled CRTh2 antagonists have used nonphysiologic assay conditions, experiments being conducted at room temperature in the absence of salt (Gervais et al, 2011). Findings from these early kinetic studies are therefore likely to overestimate the receptor target coverage since it has been well documented that compound kinetics is highly dependent on temperature and sodium ion concentration (Sykes et al, 2012). This phenomenon was also apparent in the current study, with the off rates of QAW039 and OC-459 being up to 5-fold slower when measured at room temperature compared with 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it was shown that the duration of the bronchodilator action in vivo of different muscarinic antagonists resembles their residence times at M 3 receptors determined in vitro under nonphysiologic conditions (Gavaldà et al, 2014). However, other factors, particularly rebinding of the dissociated drug to receptors in the effect compartment, seem likely to contribute to the long duration of action of LAMAs in vivo (Sykes et al, 2012).…”
Section: Examples For Biologic Discrimination By Different Ligand Resmentioning
confidence: 99%
“…This problem also extends to data fitting procedures, because often researchers use very simple kinetic models to fit the data that do not account for such details (Motulsky and Mahan, 1984). Furthermore, radioligand binding assays are often conducted on ice and in nonphysiologic buffer conditions, and it has been shown that 10-fold shorter residence times of tiotropium at the M 3 acetylcholine receptor are obtained under physiologic conditions (Sykes et al, 2012). Label-free approaches (see next section) have also been used to study ligand protein interaction kinetics using purified proteins and immobilization strategies.…”
Section: State Of the Art: Currently Used Assaysmentioning
confidence: 99%